Design and Development of Vehicle for Armless Physically Challenged Persons - S.Rajendran, V.Chokkalingam, D. Loganathan, M.Arulmurugan, G. Murugesan (Mathematical Statistician and Engineering Applications, 2023)
Transportation is one of the most important sources for increasing mobility of humans and it plays a major role in human life. Normal human being uses vehicles easily but for a disabled person it is not possible. There are many ways to make transportation easier for the people with disabilities who may wish to drive by themselves as others on the road. People with disabilities in limbs have difficulties in travelling and cannot travel long distances. They use devices such as wheel chair, crutches, and artificial limbs for mobility. These cannot be used for long distance outdoor transportation. Modification of standard production vehicle with experimental setup enables Physically Challenged person to drive vehicles by themselves without anyone’s help. Various vehicles are available commercially for person with disabilities. Our focus is on persons who lost their hands and wish to drive vehicles on their own.